Simulation of a MicroMegas detector for low-energy α-particle tracking using Garfield++ - Davis, Marios; Diakaki, Maria; Kokkoris, Michael; Michalopoulou-Petropoulou, Veatriki; Vlastou, Roza (HNPS Advances in Nuclear Physics, 2022)
In the present work, the simulated detector was a MicroMegas gaseous one, regularly being used for neutron-induced fission studies at NCSR ‘Demokritos’. The initial code tests involved the linear response of the detector with respect to the energy deposition of 5 MeV α-particles. This study was carried out in two distinct steps: First, by collecting simulated data for the deposited charge in the anode electrode for different particle trajectories, as well as, for the same trajectory, but for different gas pressures, ranging between 0.8 and 1.2 atm and then by comparing them with the corresponding results obtained using SRIM2008 regarding the α-particle energy losses inside the detector, with the same set of parameters. Finally, a simulated spectrum of 5 MeV α-particles, having trajectories randomly distributed within the whole detector volume, was obtained using Garfield++ and was compared to an experimental one. The similarities and discrepancies observed are discussed and analyzed.